Experimental validation of the hyperpolarized 129Xe chemical shift saturation recovery technique in healthy volunteers and subjects with interstitial lung disease. Issue 1 (8th August 2014) - Stewart, Neil J.; Leung, General; Norquay, Graham; Marshall, Helen; Parra‐Robles, Juan; Murphy, Philip S.; Schulte, Rolf F.; Elliot, Charlie; Condliffe, Robin; Griffiths, Paul D.; Kiely, David G.; Whyte, Moira K.; et al.
<x xml:space="preserve">Abstract</x> Purpose To assess the sensitivity of the hyperpolarized 129Xe chemical shift saturation recovery (CSSR) technique for noninvasive quantification of changes to lung microstructure and function in idiopathic pulmonary fibrosis (IPF) and systemic sclerosis (SSc). Methods Ten healthy volunteers, four subjects with SSc and four with IPF were scanned at 1.5 T. A CSSR pulse sequence was implemented using binomial‐composite radiofrequency pulses to monitor 129Xe magnetization in tissues and blood plasma (T/P) and red blood cells (RBCs). The dynamics of 129Xe uptake into these compartments were fitted with three existing analytical models of gas diffusion to extract parameters of lung physiology. These parameters were quantitatively compared between models. Results Uptake of xenon into the pulmonary capillaries was impaired in subjects with IPF and SSc. Statistically significant septal thickening was measured by 129Xe CSSR in IPF patients. Preliminary data suggests age‐dependent alterations to septal thickness in healthy volunteers. These findings were reproduced using each of the literature models. CSSR‐derived parameters were compared with gold‐standard indicators of pulmonary function; diffusing capacity of carbon monoxide and pulmonary transit‐time. Conclusions CSSR with hyperpolarized 129Xe is sensitive to pathology‐induced degradation of lung structure/function and shows promise for quantification of disease severity and monitoring treatment response. Magn Reson Med 74:196–207, 2015. © 2014 Wiley Periodicals, Inc.